The EnVision++ system: a new immunohistochemical method for diagnostics and research. Critical comparison with the APAAP, ChemMate, CSA, LABC, and SABC techniques. Issue 7 (July 1998) - Sabattini, E; Bisgaard, K; Ascani, S; Poggi, S; Piccioli, M; Ceccarelli, C; Pieri, F; Fraternali-Orcioni, G; Pileri, S A
Abstract : AIM: To assess a newly developed immunohistochemical detection system, the EnVision++. METHODS: A large series of differently processed normal and pathological samples and 53 relevant monoclonal antibodies were chosen. A chessboard titration assay was used to compare the results provided by the EnVision++ system with those of the APAAP, CSA, LSAB, SABC, and ChemMate methods, when applied either manually or in a TechMate 500 immunostainer. RESULTS: With the vast majority of the antibodies, EnVision++ allowed two- to fivefold higher dilutions than the APAAP, LSAB, SABC, and ChemMate techniques, the staining intensity and percentage of expected positive cells being the same. With some critical antibodies (such as the anti-CD5), it turned out to be superior in that it achieved consistently reproducible results with differently fixed or overfixed samples. Only the CSA method, which includes tyramide based enhancement, allowed the same dilutions as the EnVision++ system, and in one instance (with the anti-cyclin D1 antibody) represented the gold standard. CONCLUSIONS: The EnVision++ is an easy to use system, which avoids the possibility of disturbing endogenous biotin and lowers the cost per test by increasing the dilutions of the primary antibodies. Being a two step procedure, it reduces both the assay time and the workload.